Estudo de primeiros princípios de nanofios em arseneto de índio e fosfeto de índio - Santos, Cláudia Lange dos (2011)
In this work we used the density functional theory to study InAs and InP nanowires and InAs/InP nanowire heterostructures. Initially we studied the structural, electronic and mechanical properties of InAs and InP nanowires as a function of the diameter and the influence of external mechanical stress on the electronic properties of these systems. Our results show that all analyzed properties change with increasing quantum confinement. Further, the application of an external stress along the nanowire axis reveals a direct to indirect band gap transition for compressive strain in very thin nanowires. We have also studied the quantum confinement effects on the effective masses of charge carriers in InAs nanowires grown in different crystallographic directions. We found the electron and hole effective masses increase with decreasing diameter independently of the growth direction. However, in the range of the studied diameters, the hole effective mass is significantly smaller to the corresponding one at the bulk system. From the study of the stability and electronic properties of the cadmium and zinc doped InAs nanowires, we show that the Cd impurity prefers to be at the core region, whereas Zn impurity is found to be equally distributed along the nanowire diameter. The analysis of the electronic properties of these systems show that these impurities introduce shallow acceptor levels in the band gap, enabling a p-type behavior of these nanowires. Finally, we determined (i) the structural, electronic and mechanical properties of axially and radially modulated InAs/InP nanowire heterostructures for a specific diameter and (ii) the structural and electronic properties of radial InAs/InP nanowire heterostructures as a function of the diameter and composition. From (i), our calculations showed the analyzed properties have an intermediate value between those for the pure InAs and InP nanowires with similar diameters. In particular, the presence of an InP shell covering the InAs nanowires enhances the InAs electron mobility, as compared to the uncapped InAs nanowires. In addition, for the radial heterostructure, the conduction and the valence band alignments favor a type-I heterojunction, while for the axial heterostructure a transition from a type-I to a type-II heterojunction could occur at this range of diameters. From (ii), we observed that for nanowire heterostrutures of similar diameters, the variation of their structural and electronic properties with the composition possesses significant deviations from the linear behavior, which are dependent of the nanostructure diameter. The conduction band offset is approximately zero and the valence band offset decrease regardless of diameter and composition of the heterostructure.